2021
DOI: 10.1002/ccr3.4007
|View full text |Cite
|
Sign up to set email alerts
|

A case report of pneumomediastinum in a COVID‐19 patient treated with high‐flow nasal cannula and review of the literature: Is this a “spontaneous” complication?

Abstract: Oxygen support with high‐flow nasal cannula (HFNC) is gentler than mechanical ventilation and may provide significant benefits, but more studies are needed to investigate the efficacy and safety of different respiratory supports in patients with COVID‐19 pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“… 37 , 38 , 39 Few patients with COVID‐19 on high‐flow nasal cannula also developed SPM. 40 , 41 , 42 Because the alveoli of patients with COVID‐19 are more prone to rupture due to diffuse alveolar injury caused by SARS‐CoV‐2, even the lower positive end‐expiratory pressure offered by high‐flow nasal cannula might have caused SPM. On the contrary, some studies show that high‐flow nasal cannula is safe, and 74% of pneumomediastinum resolved after high‐flow nasal cannula therapy.…”
Section: Treatment Of Spontaneous Pneumomediastinummentioning
confidence: 99%
See 1 more Smart Citation
“… 37 , 38 , 39 Few patients with COVID‐19 on high‐flow nasal cannula also developed SPM. 40 , 41 , 42 Because the alveoli of patients with COVID‐19 are more prone to rupture due to diffuse alveolar injury caused by SARS‐CoV‐2, even the lower positive end‐expiratory pressure offered by high‐flow nasal cannula might have caused SPM. On the contrary, some studies show that high‐flow nasal cannula is safe, and 74% of pneumomediastinum resolved after high‐flow nasal cannula therapy.…”
Section: Treatment Of Spontaneous Pneumomediastinummentioning
confidence: 99%
“…However, SPM was reported with the use of high‐flow nasal cannula in adults and the pediatric population before the COVID‐19 pandemic 37–39 . Few patients with COVID‐19 on high‐flow nasal cannula also developed SPM 40–42 . Because the alveoli of patients with COVID‐19 are more prone to rupture due to diffuse alveolar injury caused by SARS‐CoV‐2, even the lower positive end‐expiratory pressure offered by high‐flow nasal cannula might have caused SPM.…”
Section: Treatment Of Spontaneous Pneumomediastinummentioning
confidence: 99%
“…It becomes critical when acute respiratory distress syndrome (ARDS), shock, or multiple organ dysfunction syndrome (MODS) are presented. Although the three most common symptoms of COVID-19 are fever (99%), fatigue (70%), and dry cough (59%) [25][26][27], it has also been reported that the presence of fever varies according to patient characteristics. Indeed, fever is often more frequent during hospitalization compared to actual hospital admission (89% vs. 44%) [28].…”
Section: Pathogenesis and Different Organ Involvementmentioning
confidence: 99%
“…Coronavirus disease (COVID‐19) due to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection mainly causes lung injury in patients and requires mechanical ventilation if it leads to acute respiratory distress syndrome (ARDS). In patients with COVID‐19, pneumomediastinum has been increasingly reported in cases of noninvasive oxygen therapy, including high‐flow nasal cannula, 1 , 2 and invasive mechanical ventilation. 3 , 4 However, its pathogenesis is not well understood yet.…”
Section: Introductionmentioning
confidence: 99%